Input Analysis and Marketing of Oyster Mushrooms - oddo, irenius; Handayawati, Hani Sri; Sari, Risca Kurnia (University of Brawijaya, 2020)
The aim of this study is to analyze the production and marketing input of oyster mushrooms in Sumberagung Village, Ngantang District, Malang Regency, which was conducted in August 2019. The method used in this study was exploration and direct interviews with the oyster mushroom entrepreneurs. Data were analyzed using business effectiveness (R/C) analysis, ROI or Return On Investment analysis and marketing effectiveness analysis. The results show that oyster mushroom production inputs were all forms of input such as production facilities and infrastructure, capital and business costs for oyster mushrooms, labor and production sites. Oyster mushroom marketing system was carried out starting from harvesting, post-harvest and marketing activities that were still simple and traditional. Analysis of business effectiveness (R/C), ROI analysis or Return On Investment and analysis of marketing effectiveness of the initial period of oyster mushroom business shows that the use of oyster mushroom business input such as initial capital is economically ineffective but the following period of venture capital is effectively business (R/C), ROI or Return On Investment analysis and marketing effectiveness analysis are effective.